Digital-Driven Design Thinking as a Catalyst for Enhancing Operational Efficiency and Environmental Sustainability in Oil and Gas Industry. (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Today, the Nigerian oil and gas industry is grappling with several issues, including operational inefficiency, environmental sustainability, and the need for digital transformation. Traditional engineering solutions are inadequate when dealing with the complex interplay between technological innovation, human-centred problem solving and sustainable operational practices. This study was designed to investigate the application of digital driven DT within the Niger Delta region of Nigeria for the benefit of the operation of the oil and gas organizations to minimize impact on the environment and enhance the organization's operation. The study employed a cross-sectional survey research design, which was quantified. The total population and sample size were 420 and 205, respectively, while the retrieved questionnaire and valid responses were 195 and 188, respectively. Pearson correlation and multiple regression analyses were employed for data analysis. The results showed that digital experimentation has a tremendous positive impact on operational efficiency, with predictive maintenance, process optimization, and less downtime. Human-centred digital problem solving proved to be a very good predictor for operational efficiency, since it supports adaptive decision-making and employee participation. The research revealed that cross-functional digital collaboration will have a positive impact on environmental sustainability aspects, such as emissions monitoring, coordinated decision-making and resource optimization. The paper applies digital-driven DT to the oil and gas industry and shows that for sustainable operational performance, it is not enough to adopt the technology, but organisations must have collaborative and human-centred processes.